The Analyze of relationship between income structure and household income distribution of the people Namor District, Oudomxay Province - CHANHTANGUEN , Chanhmany; SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; SENGDARA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The research entitled "An analysis of the relationship between income structure and distribution of household income of the people of Namor District, Oudomxay Province" aims to analyze the distribution of household income with a sample group of 224 households using Gini coefficient statistics to analyze the data. The results showed that the average household member is 7. The majority of household members’ age is under 20 years old. Most of them are married and have completed primary and secondary education. The members that can generate income for a family is around 3-4 people. The main household economic activity is agricultural production. The main purpose of agriculture is to consume and sell to the locals. The average income is between 8,000,000-150,000,000 LAK. Through the analysis of the relationship between the income structure of each sector and the total income, it showed that the total income is related or depends on the income from the agricultural production more than others with a correlation coefficient of 0.875 and the income from rubber plantations, income from salary, income from daily labor and other income (i.e. income from lottery) have an effect on the equality of income distribution with a statistical significance level at 0.01. The income from the sale of forest products of Dong and herbal medicine and income from weaving clothing, has an effect on the equality of income distribution with the statistical significance level at 0.05. In terms of the income from farming, industrial-craft production and all types of repair service operations, they affect the equality of income distribution with the statistical significance level at 0.1, and it can also be seen that the structure of income from agricultural production has the highest correlation ratio to income distribution, which is 27.5%, even though the average income from agricultural production is less than other sectors.